Catholic Contributions to Bioethics: Reflections on Evangelium Vitae - Reddy Alla, Stanislaus Subba (Asian Horizons, 2010)
Baiju Julian and Hormis Mynatty, eds., Catholic Contributions to Bioethics: Reflections on Evangelium Vitae, Bangalore: Asian Trading Corporation, 2007. Pages: xxii+464. ISBN: 81-7086-408-9.